Determinants of alcohol consumption among adolescents: is mindfulness a predictor factor? - Arıcı Gürbüz, Asiye; Akdağ, Berhan (Journal of Dependence, 2025)
Objective: While the relationship between mindfulness and alcohol consumption is well-documented in adults, it remains underexplored in adolescent populations. This study aimed to examine the predictive role of mindfulness in alcohol consumption among adolescents.Method: The study included a cohort of adolescents (n = 70) receiving care at a child and adolescent psychiatry outpatient clinic who reported alcohol use. Participants completed a series of validated measures during face-to-face interviews, including the Child and Adolescent Mindfulness Measure (CAMM), the Kessler–10 Psychological Distress Scale (K10), the Drinking Motives Questionnaire–Revised–Coping Motives (DMQ–R–CM), and the Alcohol Use Disorders Identification Test–Consumption (AUDIT–C).Results: The mean participant age was 16.99 years, with 54.3% being male. Female gender was a significant negative predictor of DMQ–R–CM scores (B = –3.936, p = .022), whereas higher K10 scores were positively associated with DMQ–R–CM scores (B = .280, p = .002). Additionally, both the duration of alcohol use (B = .861, p
Keywords: Adolescent; coping motives; mindfulness; psychological distress; problematic alcohol use